The relationship between quality of life and the use of immunobiologicals in patients with psoriasis - Lócio, Aline Moreira; Paiva, Lara Maria de Oliveira; Bastos, Lêda Maria Veloso; de Oliveira, ⁠Luciana Maria Pereira (Seven Editora, 2024)
This study investigated the relationship between quality of life and the use of immunobiologicals in patients with psoriasis. In order to assess how these therapies affect the daily lives and well-being of patients, a cross-sectional study was conducted at the General Hospital of Fortaleza between September 2023 and June 2024, with 29 patients with psoriatic arthritis. Using a questionnaire based on the Psoriasis Life Quality Index (DLQI), two groups were compared: those who used immunobiologicals and those who did not. The results showed that, although treatment with immunobiologicals offers effective control of the disease, the impact on quality of life varied. In particular, the use of immunobiologicals was associated with a significant improvement in the ability to play sports. However, the overall psychosocial impact seemed attenuated, possibly due to the patients’ long time with the disease and their familiarity with its condition. Limitations of the study include the small sample size and the difficulty of evaluating patients with active disease. It is concluded that, while immunobiological therapy can improve specific aspects of quality of life, further research is needed in future research to better understand the impact of these therapies on different stages of psoriasis and to develop more comprehensive approaches. DOI:https://doi.org/10.56238/sevened2024.018-040